2004
DOI: 10.1080/02841860310018990
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in surgical stage I endometrial carcinoma

Abstract: The prognostic impact of DNA ploidy, MIB-1 and p53 was evaluated in relation to clinical and histopathological features in surgical stage I endometrial carcinoma (n = 284) and in the histopathological endometrioid subgroup (n = 257). Tumour material from 284 consecutive patients was analysed regarding image cytometric DNA ploidy and the immunohistochemical MIB-1 and p53 expression. Twenty-four tumours relapsed. In univariate analysis, histopathological subgroup (endometrioid vs. non-endometrioid), grade, DNA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
0
24
0
6
Order By: Relevance
“…Along with the fact of more significant spots between samples of the same histopathology but different ploidy status, we suggest that aneuploidy could be of greater impact regarding poor prognosis than the histological subtype. Interpretations from other data also highlight the importance of aneuploidy for the prognosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Along with the fact of more significant spots between samples of the same histopathology but different ploidy status, we suggest that aneuploidy could be of greater impact regarding poor prognosis than the histological subtype. Interpretations from other data also highlight the importance of aneuploidy for the prognosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, investigators have verified the existence of p53-positive tumors with an endometrioid pattern, and in one study, p53 emerged as an important prognostic marker in this subset. 14,15 In view of the prognostic significance of p53 immunostaining with outcome, this marker has been proposed by some as a useful adjunct in the classification of selected endometrial adenocarcinomas. Based on this study, a proportion of endometrial carcinomas can be expected to pose a problem in classification for a practicing pathologist, or be classified discordantly by two or more pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…Ploidy has been evaluated as prognostic factor in a number of studies and shown to be an independent prognostic factor in some of these [2,4 Á8]. Still only a limited number of aneuploid tumours relapse [2,5] which does not make it an optimal prognostic factor. Other attempts to evaluate genetic instability or its consequences have been made in order to find possible future prognostic factors.…”
Section: Discussionmentioning
confidence: 99%